Location of Seismic "Hum" Sources Following Storms in the North Pacific Ocean. (18th March 2019) - Maurya, Satish; Taira, Taka'aki; Romanowicz, Barbara
Abstract: We investigate the spatially and temporally varying distributions of sources of the Earth's low‐frequency seismic hum at high space‐time resolution during a seismically quiet 7‐day period in December 2015, when two large storms with different reaches propagate across the North Pacific Ocean. We integrate information from a variety of data from ocean wave height, infragravity wave prediction model, and broadband seismic data. We analyze seismic data to understand the seismic hum better: power spectral density at stations for detection and location of sources using array beamforming and backprojection methods, with a 3‐hr temporal and 5° spatial resolution. For storms propagating west to east across the northern Pacific hitting the west coast of North America broadscale, we show that the distribution of hum sources is consistent with a model of seismic energy generated via infragravity waves, produced near the impact location of the storm, and propagating along the coast as well as toward the open ocean. The generation of seismic hum depends strongly on the reach of the storm and is very weak for a storm with more northerly propagation toward Alaska. At shorter periods (e.g., 70 s), the seismic hum is generated in a narrow band that follows the coast, reaching progressively further to the north, while at longer periods (e.g. 150 s), it covers a broader area reaching far into the deep ocean. It may thus be possible to predict the distribution of the strongest "hum" sources, to first order, from the knowledge of the direction of propagation and strength of northern Pacific storms. Plain Language Summary: The Earth's low‐frequency "hum" originates primarily in the oceans and is generated through the interaction of infragravity waves (IG) with the seafloor. However high‐resolution spatial and temporal distribution of hum remains unclear. We study a 6‐day‐long time window devoid of large earthquakes in December 2015, when two distinct large storms originate in the western Pacific, and propagate across the northern Pacific Ocean, generating IG waves and hum as they reach the coasts. Using array beamforming and backprojection approaches, our results show the striking difference in the hum generated by the two storms: the first one initially generates strong hum along the Cascadia coast, progressively extending toward Alaska and the Aleutians, while at the longest periods (e.g., 150 s) it also reaches the open ocean basins. This provides a strong indication that both shallow and deep water IG waves propagating far from their source are responsible for the generation of the observed hum. In contrast, the second large storm generates hum only briefly, and the sources are mostly confined to the near coast in Alaska. Key Points: High‐resolution analysis of hum generated by storms in the northern Pacific indicates consistency with a model of generation via infragravity waves The generation of seismic hum depends strongly on the reach of causative storms Shorter‐period hum is generated along the coast; longer‐period hum sources extend into ocean basins